The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1002/jhm.2674
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and Outcomes of Fasting Orders Among Medical Inpatients

Abstract: While many hospitalized patients have orders to fast in preparation for interventions, the extent to which these orders are necessary or adhere to evidence-based durations is unknown. In this study, we analyzed the length, indication, and associated outcomes of nil per os (NPO) orders for general medicine patients at an academic institution in the United States, and compared them to the best available evidence for recommended length of NPO. Of 924 NPO orders assessed, the indicated intervention was not perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…[22] Better education of the clinical team on pre-procedure fasting guidelines may help mitigate prolonged nil per os. [13,[22][23][24] Due to the unique nature of our study, there is limited ability to compare our findings with previous studies. Additionally, due to limited resources, our study had a small sample size and therefore lack of association between readmission and gaps in care may be due to type 2 error.…”
Section: Discussionmentioning
confidence: 94%
“…[22] Better education of the clinical team on pre-procedure fasting guidelines may help mitigate prolonged nil per os. [13,[22][23][24] Due to the unique nature of our study, there is limited ability to compare our findings with previous studies. Additionally, due to limited resources, our study had a small sample size and therefore lack of association between readmission and gaps in care may be due to type 2 error.…”
Section: Discussionmentioning
confidence: 94%
“…Of note, our study showed that only 36% of patients received proper instructions about preparing for fasting for labs. We have not found literature addressing if patients with diabetes are educated or informed when fasting labs are ordered, except for sporadic reports [ 21 23 ]. A small study by Kackov and associates has found that the majority of outpatients are not well informed about how to fast for lab tests [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Only 15% and 19% of patients reported that they were properly informed by a doctor or a nurse, respectively, about preparation for fasting for labs. Furthermore, few other investigators addressed inpatient fasting orders (for various indications) and raised concerns about the appropriateness of these orders [ 22 ], as well as the potential risk of hypoglycemia in patients with diabetes [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a different meta‐analysis, it was shown that about 50% of the meals held for patients could have been served . Such prolonged perioperative/periprocedure fasting has been shown to increase the risk for complications and is often unnecessary …”
Section: Discussionmentioning
confidence: 99%
“…18 Such prolonged perioperative/periprocedure fasting has been shown to increase the risk for complications and is often unnecessary. 19,20 In an effort to improve excessive time spent NPO for procedures or testing, we are proposing that physicians be required to document the purpose for NPO status within the patient's order. This would give staff more clarity as to when food could be served postprocedurally.…”
Section: Discussionmentioning
confidence: 99%